2008
DOI: 10.1080/13880200802215784
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Extracts in Relationship to Structure of Pure Isolates ofAbutilon indicum

Abstract: The present investigations were undertaken to determine the antibacterial and antifungal activity of the crude extract (CE) of plant parts of Abutilon indicum L. (Malvaceae) in relation to the structure of all previous isolates active and inactive against three Gram-negative bacteria, four Gram-positive rods, and three fungi using agar diffusion method. The results suggested some importance and influence of the hydroxyl groups in the isolates structures such as steroids, flavonoids, glycerides, and coumarins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Yasmin et al (2008) reported that the root parts of A. indicum exhibited greater antibacterial activity against Micrococcus luteus, Bacillus subtilis, Escherichia coli and Bacillus licheniformis compared to the leaf and seed extracts, which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Yasmin et al (2008) reported that the root parts of A. indicum exhibited greater antibacterial activity against Micrococcus luteus, Bacillus subtilis, Escherichia coli and Bacillus licheniformis compared to the leaf and seed extracts, which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…The major components of A. indicum seed oil were identified as linoleic, oleic, stearic and palmitic acids, and this result is consistent with earlier reports (Sharma et al, 2013). These oil components promoted antioxidant activity, as reported in previous studies (Yasmin et al, 2008;Tripathi et al, 2012), and oleic acid may also play an important role in the treatment of heart disease (Singh and Gupta, 2008).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations